First description of the ichnofauna from the type locality of the Famennian stage (Late Devonian) of S Belgium. Issue 4 (1st October 2020) - Morelle, Cassian; Denayer, Julien
Abstract: Ichnofossils from the type locality of the Famennian are here described and figured for the first time. The siliciclastic supratidal alluvial to proximal subtidal deposits of S Belgium yield a diverse ichnofauna composed of Arenicolites ispp. (two morphotypes), Chondrites intricatus, Diplocraterion isp., Dolopichnus gulosus, Gordia marina, Helminthopsis isp., Lockeia cordata, L. siliquaria, Palaeophycus tubularis, P. sulcatus, Planolites isp., Protovirgularia obliterata, P. cf. rugosa, P. isp. and Psammichnites implexus. As a whole, these 16 ichnospecies and 11 ichnogenera form the typical assemblage of the Cruziana ichnofacies where Palaeophycus is largely dominant. However, the Belgian Famennian displays a large range of lithofacies corresponding to various environments in which distinct ichnofossil assemblages are identified. Arenicolites isp. collected from sabkha-type primary dolomite indicates the probable colonisation of hypersaline environment by Arenicolites tracemakers as early as the Late Devonian. The type material of Crossochorda marioni Dewalque, 1881 is revised and attributed to Protovirgularia obliterata and P . cf. rugosa.